(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
The sorbtiv exception of iodine is described of polyurethan foams on the basis of ethers, естерів and them copolymers from high mineral geothermal waters of the Crimean peninsula.